Setting up the HyDRA blind challenge for the microhydration of organic molecules. Issue 19 (6th May 2022) - Fischer, Taija L.; Bödecker, Margarethe; Zehnacker-Rentien, Anne; Mata, Ricardo A.; Suhm, Martin A.
Abstract : The first theory blind challenge addressing the effect of microsolvation on water vibrations is launched. Abstract : The procedure leading to the first HyDRA blind challenge for the prediction of water donor stretching vibrations in monohydrates of organic molecules is described. A training set of 10 monohydrates with experimentally known and published water donor vibrations is presented and a test set of 10 monohydrates with unknown or unpublished water donor vibrational wavenumbers is described together with relevant background literature. The rules for data submissions from computational chemistry groups are outlined and the planned publication procedure after the end of the blind challenge is discussed.